Comparative Analysis Of Continuous And Interrupted Suturing Techniques In Urethroplasty For Hypospadias - Aziz, Kamran; Aleem, Asra; Saeed, Safdar; Jamal, Muhammad Rashid; Shah, Ijaz Hussian; Siddiqui, Sana Shaukat (Journal of Rawalpindi Medical College, 2025)
Objective: Hypospadias is one of the most frequent congenital anomalies in males that affects penile development and hence optimal urine and semen flow. Snodgrass Tubularized Incised Plate Urethroplasty (TIP) is a widely employed technique for hypospadias, done in a single stage. While both continuous and interrupted sutures are options for TIP procedures, the best technique for minimizing complications is still under debate. Methods: A quasi-experimental study was carried out in the Urology department of DG Khan Medical College and Hospital from June 2022 to June 2023 that included 69 boys divided into 2 groups based on suturing technique: 37 boys underwent continuous-suture Snodgrass TIP urethroplasty and 32 boys underwent interrupted-suture Snodgrass TIP urethroplasty. The ethical protocol was followed throughout the period. Results: The mean age was 9.12 years, and we found that there was a statistically significant association between the type of complication and the suturing technique (p=0.117). Meatal stenosis (MS), urethral stricture, and urethrocutaneous fistula (UF) did not exhibit significant differences between groups (p-values > 0.05). Compared to patients with complications (53.6%), those without complications had a significantly higher chance of having a healthy single urine stream (100%). Conclusion: Our findings suggest that interrupted suturing in TIPU may be associated with fewer complications and a higher rate of single urine stream compared to the continuous suturing technique. Keywords: Hypospadias, Urethra, postoperative complications, Suturing Techniques.